Scrum For Dummies - Layton, Mark C. (John Wiley & Sons, 2015)
Practice an agile form of management to stop wasting time and money Sc rum For Dummies is an easy to use guide to managing the tricky transit ion from a traditional project management methodology to the new and m ost popular agile framework. As the most efficient, successful methodo logy for team project management, Scrum relies on transparency, flexib ility, and fluidity to deliver a final product that fulfills the needs of all stakeholders. Written in easy–to–read Dummies style, this book walks you through the core principles of Scrum and provides a roadmap for tangible implementation. The vast majority of projects go over bu dget, and billions of dollars are wasted every year on overruns. Put a stop to this wasteful leakage by switching to a management style that keeps all participants informed, up–to–date, and accountable. Authore d by a Certified Scrum Trainer, Mark Layton, Scrum For Dummies covers the key ideas and processes behind Scrum methodologies, and presents t he inner workings of the plan in an engaging and accessible format. To pics include: The Scrum values, roles, artifacts, and activities that make up the principle of this methodology When and how best to use Scr um The differences between Scrum and other agile methodologies Using S crum for IT, finance, construction, health care, and more The book als o delves into the everyday use of Scrum, and how it can help you achie ve your own personal goals outside of work. There's a reason why scrum is quickly becoming the standard approach to project management it wo rks! If you want to stop wasting time and start producing more effecti vely, Scrum For Dummies is the guide that will get you there.